Sosialisasi Penggunaan Internet yang Sehat bagi Anak-Anak di yayasan Domyadhu - Wiwi Apriyanti Wiwi; Erni; Muchlas Syahlanisyiam; Yolanda Anggraini; Sahrul Gunawan; Rinawang Tyas Arinanto; Rahnat Adnan Fauzan; Nuryanti Tuto Suban; Asmat; Affandi Agung (Abdi Jurnal Publikasi, 2022)
Community service is an activity that aims to help the community in the form of activities in any form. Community Service Activities are a part of Pamulang University. The author carried out this PKM activity with the title